Recovery of lithium and cobalt from lithium cobalt oxide and lithium nickel manganese cobalt oxide batteries using supercritical water - Barros, Thiago V. (2024)
This study investigates the eco-friendly extraction of metal oxides from LCO and NMC batteries using supercritical water. Experiments were conducted at 450 °C with a feed rate of 5 mL min−1 and varying battery/PVC ratios (0.0, 2.0, and 3.0). The products were analyzed by X-ray diffractometry (XRD), atomic absorption spectrometry (FAAS) and gas chromatography-mass spectrometry (GC-MS). Results show the presence of cobalt chloride (CoCl2) and lithium (Li) in the liquid products, achieving 100% cobalt recovery under all conditions. The gaseous products obtained hydrogen with molar compositions up to 78.3% and 82.7% for LCO:PVC and NMC:PVC batteries, respectively, after 60 min of reaction. These findings highlight the potential of this methodology for lithium-ion battery recycling.